2022
DOI: 10.3389/fonc.2022.780078
|View full text |Cite
|
Sign up to set email alerts
|

The Apparent Diffusion Coefficient of Diffusion-Weighted Whole-Body Magnetic Resonance Imaging Affects the Survival of Multiple Myeloma Independently

Abstract: BackgroundDiffusion-weighted whole-body MRI (DW-MRI) is increasingly used to evaluate bone diseases of multiple myeloma (MM), but there is lack of quantitative indicator for DW-MRI to reflect the prognosis of MM. Apparent diffusion coefficient (ADC) values in DW-MRI has potential correlations between some indexes of MM, but the influence of ADC on MM survival needs to be further verified.MethodsA total of 381 newly diagnosed MM patients were enrolled in the study to analyze the effect of ADC values in DW-MRI o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
4
2
Order By: Relevance
“…31 Several studies have shown a prognostic value for the ADC value in multiple myeloma, as an independent prognostic predictor of PFS and OS. [32][33][34] However, this work indicated ADC was not an independent prognostic factor of HRMM by multivariate analysis. This might be because various factors affect the ADC value, including the number of yellow bone marrow cells, cell size, cell structure, and/or perfusion effects.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…31 Several studies have shown a prognostic value for the ADC value in multiple myeloma, as an independent prognostic predictor of PFS and OS. [32][33][34] However, this work indicated ADC was not an independent prognostic factor of HRMM by multivariate analysis. This might be because various factors affect the ADC value, including the number of yellow bone marrow cells, cell size, cell structure, and/or perfusion effects.…”
Section: Discussioncontrasting
confidence: 61%
“…Several studies have shown a prognostic value for the ADC value in multiple myeloma, as an independent prognostic predictor of PFS and OS 32–34 . However, this work indicated ADC was not an independent prognostic factor of HRMM by multivariate analysis.…”
Section: Discussioncontrasting
confidence: 55%
“…Studies have shown that DW-MRI can detect more focal lesions compared to conventional radiography and has a high concordance with the bone marrow plasma cell infiltration rate [36], [38]. Additionally, changes in ADC values post-treatment have been correlated with response to chemotherapy, with responders showing a significant increase in ADC values, indicating a reduction in cellularity and a positive treatment effect [39], [44].…”
Section: Dw-mrimentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) as part of whole-body magnetic resonance imaging (wb-MRI) is of great clinical value in imaging of MM patients 3,4 and is increasingly recommended for both initial workup and follow-up imaging 5–8 . Diffusion-weighted imaging allows assessment of the semiquantitative apparent diffusion coefficient (ADC), which has been shown to correlate with histology 9,10 and to differ significantly between the different stages of monoclonal plasma cell disorders, 9–11 between different classes of therapy response, 9,12–21 and to be of predictive value for progression-free survival and overall survival 22,23 . The texture of the bone marrow is very heterogenous, and there is a large volume of bone marrow in which a region of interest (ROI) can be placed when the ADC is manually measured by radiologists.…”
mentioning
confidence: 99%
“…[5][6][7][8] Diffusion-weighted imaging allows assessment of the semiquantitative apparent diffusion coefficient (ADC), which has been shown to correlate with histology 9,10 and to differ significantly between the different stages of monoclonal plasma cell disorders, [9][10][11] between different classes of therapy response, 9,[12][13][14][15][16][17][18][19][20][21] and to be of predictive value for progression-free survival and overall survival. 22,23 The texture of the bone marrow is very heterogenous, and there is a large volume of bone marrow in which a region of interest (ROI) can be placed when the ADC is manually measured by radiologists. Consequently, the test-retest repeatability and interrater reproducibility using ROI-based ADC measurements in the bone marrow have been reported to be relatively low, especially in comparison to other tissues.…”
mentioning
confidence: 99%